CHILDREN IN ALCOHOL ABUSERS’ FAMILY: PROBLEMS AND METHODS OF HELP - Kotova, Liubov (Socialinė teorija, empirija, politika ir praktika, 2009)
Alcohol abusers’ children differ from their peers coming from pro-social families. Therefore, it is important to find out the factors determining the differences in character and patterns of behavior of children from alcohol addicts’ families, as well as the psychosocial problems and the impact of their parents’ alcohol misuse on their performance at school. Only having such information one can analyze ways of helping these children. The purpose of this paper is to find out way of helping children of alcohol abusers. The way of alcohol abuser’ living makes the whole family dependent. Relationships between family members are unbalanced. Either psychological or physical violence against women and children is frequent, as well as divorce. Children of alcohol abusers have no possibility to live ordinary human development. They mature much earlier, since they have to take parents’ responsibilities. Children of alcohol abusers psychosocial functioning is unbalanced. They have learning difficulties, because of family troubles lost their learning motivation. Children of alcohol abusers interaction is limited. They do not communicate with their contemporaries. Avoid relationship with classmates and teachers. The help they get are psychological help. The main gain of which is to train the children to adapt to the way of family living. But this does not help in real. If one wants to solve their problems, one should help the whole family. Suggested is psychosocial network of help, which link different help organization, all methods of help together to help the whole family.